Cost and cost distribution of policy-driven investments in decentralized heating systems in residential buildings in Germany - Berit Hanna Czock; Cordelia Frings; Fabian Arnold (Institute of Energy Economics at the University of Cologne (EWI), 2024)
To decrease emissions from residential buildings, Germany employs a number of policies like re- newable energy requirements, subsidies, and CO2 prices that incentivize heating decarbonization. This paper analyses policy-driven household decision-making with regard to decentralized heating technology investment and the resulting costs. We apply a building level mixed integer linear pro- gramming model that computes optimal energy investment and operation for decentralized building energy technologies in 770 archetype buildings that represent the German residential building stock. We find that under renewable energy requirements, subsidies, CO2 prices, high medium-term gas prices, and moderately increasing electricity prices, it is optimal for many buildings to replace their fossil systems prematurely by electric heat pumps, achieving quick and substantial decarboniza- tion. However, the costs for decentralized decarbonization differ greatly between buildings: Some buildings profit from the subsidies, while others face high burdens. Especially, single family homes with recently installed gas and oil systems and inhabitants of multifamily homes potentially face high expenditures for CO2 prices. Policymakers should consider these dynamics when prioritiz- ing buildings for district heating or hydrogen in the municipal heat planning processes and when designing CO2 price revenue recycling mechanisms.
Keywords: C53; C54; D15; D30; H20; Q48; 330; emission reduction; building sector; building stock; household heating; CO2 pricing; building policy; MILP; archetype buildings; subsidies; decentralized technologies